The development of COVID-19 treatment - Yuan, Yongliang; Jiao, Baihai; Qu, Lili; Yang, Duomeng; Liu, Ruijuan (Frontiers in Immunology, 2023)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a pandemic of coronavirus disease 2019 (COVID-19) that has become the greatest global public health crisis of this century. Recent studies have unraveled numerous mysteries of SARS-CoV-2 pathogenesis and largely improved the development of vaccines and treatment of COVID-19. However, important questions remain regarding its therapy. In this review, we quickly summarize recent advances in our understanding of the COVID-19 mechanism. We mainly discuss current therapy strategies for COVID-19, with an emphasis on antiviral agents, neutralizing antibody therapies, Janus Kinase inhibitors and steroids. When necessary, specific mechanisms and the history of therapy are present and representative strategies are described in detail. Finally, we discuss key outstanding questions regarding future directions of the development of COVID-19 treatment.